2023
DOI: 10.3390/cells12101444
|View full text |Cite
|
Sign up to set email alerts
|

An Insight into Survivin in Relevance to Hematological, Biochemical and Genetic Characteristics in Tobacco Chewers with Oral Squamous Cell Carcinoma

Abstract: Background: Survivin is an inhibitor of apoptosis protein (IAP), encoded by the Baculoviral IAP Repeat Containing 5 (BIRC5) gene located on q arm (25.3) on chromosome 17. It is expressed in various human cancers and involved in tumor resistance to radiation and chemotherapy. The genetic analysis of the BIRC5 gene and its protein survivin levels in buccal tissue related to oral squamous cell carcinoma (OSCC) in South Indian tobacco chewers has not been studied. Hence, the study was designed to quantify survivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 115 publications
0
3
0
Order By: Relevance
“…Herein, we constructed a nanosystem consisting of aptamer-modified artificial vesicles, hMNs, and two gene therapy agents DNAzymes for RB-targeted fluorescence/magnetic resonance (FL/MR) dual-modality imaging and dual gene silencing therapy (Scheme ). In this study, two DNAzymes were used as gene therapy agents to overcome the limited effect of single gene therapy, targeting RB antiapoptotic factors Bcl-2 and Svv mRNA for simultaneous silencing and synergistic stimulation of apoptosis . The hMNs nanocarrier was GSH sensitive, which simultaneously acted as a precursor of DNAzyme cofactor and quencher of fluorophore-modified DNAzymes, facilitating intracellular DNAzyme catalysis and FL/MR imaging analysis .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, we constructed a nanosystem consisting of aptamer-modified artificial vesicles, hMNs, and two gene therapy agents DNAzymes for RB-targeted fluorescence/magnetic resonance (FL/MR) dual-modality imaging and dual gene silencing therapy (Scheme ). In this study, two DNAzymes were used as gene therapy agents to overcome the limited effect of single gene therapy, targeting RB antiapoptotic factors Bcl-2 and Svv mRNA for simultaneous silencing and synergistic stimulation of apoptosis . The hMNs nanocarrier was GSH sensitive, which simultaneously acted as a precursor of DNAzyme cofactor and quencher of fluorophore-modified DNAzymes, facilitating intracellular DNAzyme catalysis and FL/MR imaging analysis .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, two DNAzymes were used as gene therapy agents to overcome the limited effect of single gene therapy, targeting RB antiapoptotic factors Bcl-2 and Svv mRNA for simultaneous silencing and synergistic stimulation of apoptosis. 44 The hMNs nanocarrier was GSH sensitive, which simultaneously acted as a precursor of DNAzyme cofactor and quencher of fluorophore-modified DNAzymes, 45 facilitating intracellular DNAzyme catalysis and FL/MR imaging analysis. 46 For enhancing the biocompatibility and stability in vivo of DNAzymes and hMNs composite nanoparticles (Dual/hMNs), an EG-derived artificial vesicle was applied to wrap Dual/hMNs to form EG@Dual/hMNs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Studies have found that nicotine, a major component of tobacco, can affect the expression of the Bcl-2 family proteins in lung cancer cells, promoting cancer cell growth and enhancing drug resistance ( 10 , 11 ). Tobacco activates the Notch signaling pathway to induce lung cancer and regulates cell apoptosis by increasing survivin expression, thereby promoting the malignant transformation of bronchial epithelial cells ( 12 ). Vellichirammal et al reported a positive correlation between smoking and fusion frequency in lung adenocarcinoma and found that as a fusion gene associated with cigarette smoke exposure, downregulation of the P53 pathway resulted in higher gene fusion formation in lung adenocarcinoma ( 13 ).…”
Section: Introductionmentioning
confidence: 99%